Women’s autonomy and maternal health service utilization in Birendranagar Municipality of Western Nepal - Bhattarai, Dipa; Bhattarai, Sirijana; Dewan, Pramila; Bashyal, Bhanu Bhakta; Khatiwada, Kabita (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Autonomy is the ability to obtain information and make decisions about one’s own concerns independently. Women’s autonomy in health-care decision-making is extremely important for the improvement of maternal and child better health outcomes and as an indicator of women’s empowerment. The study aimed to assess the level of women’s autonomy and its relationship with maternal health service utilization among postnatal women attending an immunization clinic in Birendranagar municipality, Surkhet.Method: This descriptive cross-sectional study involved postnatal women with 45-day-old children attending an immunization clinic in Birendranagar, Surkhet. Structured questionnaires were used to interview 153 women, and the association between women’s autonomy and maternal health service use was analyzed through a chi-square test.Result: The study found that 83(54.2%) of women had low autonomy. Financial autonomy was observed in 87 (56.8%) of women, which was higher than autonomy in decision-making 51 (33.3%) and movement 47 (30.7%). Approximately 124 (81.0%) had attended four antenatal care (ANC) visits for their last pregnancy, and 149 (97.3%) delivered their last child in health facilities. However, only 25 (16.3%) attended three postnatal care (PNC) visits. There was a significant association between autonomy levels and maternal service use, particularly with ANC and PNC services (p